Neverwas [videorecording (DVD)] - Stern, Joshua Michael; Eckhart, Aaron; McKellen, Ian; Murphy, Brittany; Hurt, William; Nolte, Nick; Cumming, Alan, 1965-; Lange, Jessica; Grady, Michael; Glass, Philip (Miramax Home Entertainment : Distributed by Buena Vista Home Entertainment, 2007)
A young man finds out that his childhood fantasyland may really exist. Searching for insight into his father's life and the magical place he wrote about in the beloved children's book, Neverwas, psychiatrist Zach Riley takes a job at the institution where his father lived on and off. Once there, Zach meets Gabriel, a patient whose alternate reality is startlingly close to the world his father created.